Impacts of vegetation restoration strategies on soil nutrients and stoichiometry of the earthquake-induced landslides in Jiuzhaigou, eastern Qinghai-Tibet Plateau - Huang, Xuemei; Xian, Ting; Long, Teng; He, Li; Donald, Marion L.; Deng, Dongzhou; Dong, Tingfa (Frontiers in Environmental Science, 2024)
Natural and artificial approaches are the mainly management strategy used in degraded lands restoration, while few studies examine the effect of the two strategies on soil nutrient properties in an earthquake-triggered degraded ecosystem. We compared soil chemical traits and major nutrient stoichiometry from areas following landslides that had undergone natural restoration (D. NR.) and artificial restoration (D. AR.), as well as neighboring undisturbed areas (Und.), following the 2017 magnitude 7.0 earthquake in Jiuzhaigou, southeastern Qinghai-Tibet Plateau. The results showed that soil organic carbon (C), total nitrogen (N), available nitrogen (AN), available phosphorus (AP), exchangeable calcium (eCa), exchangeable magnesium (eMg), C/P, C/K, N/P, N/K, P/K, cation exchange capacity, and vegetation cover in landslides of D.NR. and D. AR. were lower than those in Und. land, while their pH and total potassium (K) concentration were higher. Compared to D. NR., most of these traits were higher in D. AR., except for the C/N, which was reduced in D. AR. Soil C was positively related to AN, C/K, N/P, N/K, P/K in each land type, while in D. NR., it was not related to N, AP, AK, eCa, eMg, C/N, although it was negatively related to P and K concentration. The findings demonstrated that vegetation restoration strategies could affect not only soil nutrient content but also the macronutrient stoichiometry (N, P, K). Furthermore, artificial restoration projects can enhance soil nutrient 2 concentration and facilitate vegetation recovery more quickly than natural restoration, which is primarily driven by soil N rather than P or K.